The Effectiveness of Symbolic Modeling Technique to Increase Empathy of PPA Ibnu Katsir Putri Jember Mahasantri - Zakkiyah, Zahra; Fauziyah, Nailul (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
The Effectiveness of Symbolic Modeling Technique to Increase Empathy of PPA Ibnu Katsir Putri Jember Mahasantri. This study aims to test the effectiveness of symbolic modeling techniques in increasing empathy among students of PPA Ibnu Katsir Putri Jember. The background of this study is based on the low level of empathy shown by some students in the social life of the Islamic boarding school. The study used a quantitative approach with a pre-experimental one group pre-test and post-test design method. The sample consisted of 7 students with low empathy levels selected through a purposive sampling technique. The data collection instrument was an empathy scale questionnaire, and data analysis was carried out using the Wilcoxon test. The results showed that there was a significant difference between the pre-test and post-test empathy scores with a significance value (2-tailed) of 0.018 (p <0.05), which indicates that the symbolic modeling technique is effective in increasing empathy among students. The implication of this study is the importance of implementing symbolic modeling techniques in guidance and counseling services, especially in religious education environments to shape social and moral character. Researchers recommend the continued use of this technique by counselors or Islamic boarding school administrators, as well as the development of further research with broader subjects and techniques to strengthen the understanding and application of empathy-enhancing methods among the younger generation.Keywords: Modeling Techniques; Symbolic Modeling; Empathy.